PENGARUH PERPUTARAN PIUTANG, HUTANG JANGKA PENDEK DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PT LOGAMINDO - Rio Rahmat Yusran (Bajang Institute, 2022)
The purpose this research to get tested the effect of receivable turnover, short-term debt, and firm size on the profitability in PT Logamindo Perkasa. The object were receivable turnover (X1), current ratio (X2), firm size (X3), and return on asset (Y). The result of research show that there was a positive and significant on receivable turnover, current ratio, and firm size of return on asset in PT Logamindo Perkasa with f statistic 22,045 > f table 2,77 and sig. 0,000 < 0,05. Receivable turnover have a positive and significant of return on asset with t-statistic 3,001 > t-table 2,003 and sig. 0,004 < 0,005. Current ratio have a positive and significant of return on asset with t-statistic 5,542 > t-table 2,003 and sig. 0,000 < 0,005. However firm size a negative and significant of return on asset with t-statistic -2,306 < t-table 2,003 and sig. 0,025 < 0,005